Scale-up and operating factors for electrolytic silver recovery from effluents of artisinal used-gold jewelry smelting plants in the Philippines - Alfafara, C. (Compendium of Human Ecology Researches in the Philippines, 2003)
The MMORS in the Philippines is home to many precious metal refineries, where local artisanal gold smelting industries use silver to draw gold out of used jewelry. The study aimed to explore operation and scale-up for the electrolytic recovery of silver for small-to-medium-scale used gold smelting plants. Results showed that higher silver removal rates were noted at higher operating currents. Electrodeposition a 9 amperes showed 98.7% silver recovery after 30 minutes. The charge dose for silver electrodeposition was 1.23 coulombs/mg silver ions removed, while the average electrolysis energy requirement was about 0.59 kilowatt hours/kg of silver removed. Preliminary comparisons on a 100-liter scale, showed the electrolytic process had a higher silver removal (approx 90%) compared to copper displacement (approx 65%). Results are useful for the process design of a complete field test system.